Digital Workplace Model for Research University Publication Collaboration - Bakar, N.A.A.; Ya’acob, S.; Hassan, N.H. (International Journal of Human and Technology Interaction (IJHaTI), 2018)
Digital Workplace is a virtual equivalent to the modern version of traditional workplace where an employee can work anywhere by using any devices, browsing files and sharing knowledge. Meanwhile, MyRa is commonly known as Malaysia Research Assessment tool for measuring research performance indicator in public university. The MyRA instrument is used to engage the research development and innovation activities which outcomes is categorized into six levels, with ‘six stars’ being the highest and one star the lowest. In order to achieve MyRA objective, research university boosts the research publications from academicians. However, from all submission, not all publication papers are achieved a high standard, which causes low rating stars. The absence of working digital repository for research publication is among challenge face by most academicians in searching for research paper collections as a reference. Besides that, they unable to keep in touch with the author of a research paper on getting advice and feedback for their working documents. Thus, this study aims to propose a digital workplace model focusing on research publication Digital Workplace. Initial findings highlights, there five main dimensions associated with establishing this model which are communication, environment, strategy, collaboration and community.